Thermal resistance & conduction resistance analysis of power semiconductor module - Aung, Nay Lin (2017)
Nowadays, the electric power conversion from one form to another is necessary and important in our everyday lives. Out of many power conversion devices, the Insulated Gate Bipolar Transistors (IGBTs) are popular and widely utilized in many applications such as consumer electronics, home appliances, medical equipment and transporting technology. But the functioning of IGBTs can be affected depending on numerous conditions such as temperature, electrical stress and mechanical stress. Since the usage of IGBT devices are increasing for medium to high power and medium switching frequency operations, it is critical to monitor and research on the IGBT’s ageing and degradation. This can not only help in estimating the lifetime of IGBTs but also help in reducing maintenance costs as well as preventing damages to the machines or equipment that they are used in. This research aims to understand the structure and construction of an IGBT, different degradation methods and the parameter variations of IGBT under different working environments and conditions. The first batch of IGBT modules were degraded by active power cycling method after designing and integration of DC chopper test circuit. After that, the second batch of IGBT modules were degraded by thermal cycling method. Then, key parameters such as conduction resistance, thermal resistance and power losses were measured for both degraded and good modules. These results and findings were used to create a lookup table for studying how the parameters of IGBT change with ageing process and estimating the lifetime of IGBT. Depending on popularity and applications, further experiments can be done to build lookup tables for other switching devices such as Bipolar Junction Transistor (BJT), Metal Oxide Field Effect Transistor (MOSFET), Silicon Control Rectifier (SCR) and Gate Turn Off Tyristor (GTO).